1993
DOI: 10.1104/pp.103.2.385
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Proteolysis Activates the Plasma Membrane Ca2+ Pump of Higher Plants (A Comparison with the Effect of Calmodulin in Plasma Membrane from Radish Seedlings)

Abstract: The effects of calmodulin and of controlled trypsin treatments on the activity of the Caz+ pump were investigated in plasma membrane purified from radish (Raphanus sativus 1.) seedlings. Treatment of the plasma membrane with ethylenediaminetetraacetate (EDTA), which removed about two-thirds of the plasma membrane-associated calmodulin, markedly increased the stimulation of the Caz+ pump by calmodulin. In EDTA-treated plasma membrane, stimulation by calmodulin of the Caz+ pump activity was maximal at low free C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 20 publications
(29 reference statements)
1
10
0
Order By: Relevance
“…Tryptic digestion of the cauliflower Ca2+-ATPase resulted in a Kn(Ca2+) of 0.5 p~, whereas a value of about 2 p~ was obtained with untreated membranes in the presence of CaM. In agreement with these results, it was reported that activation of the Ca2+-ATPase in radish plasma membranes by trypsin was maximal at low Ca2+ concentrations (Rasi-Caldogno et al, 1993). CaM had no effect on the V,,, or the Ca2+ affinity with trypsin-treated cauliflower membranes, as expected from the 1251-CaM-binding studies, which showed that the CaM-binding region was rapidly lost during trypsin treatment (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Tryptic digestion of the cauliflower Ca2+-ATPase resulted in a Kn(Ca2+) of 0.5 p~, whereas a value of about 2 p~ was obtained with untreated membranes in the presence of CaM. In agreement with these results, it was reported that activation of the Ca2+-ATPase in radish plasma membranes by trypsin was maximal at low Ca2+ concentrations (Rasi-Caldogno et al, 1993). CaM had no effect on the V,,, or the Ca2+ affinity with trypsin-treated cauliflower membranes, as expected from the 1251-CaM-binding studies, which showed that the CaM-binding region was rapidly lost during trypsin treatment (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…For this purpose, an antiserum was raised against the CaM-stimulated CaZf-ATPase from the low-density membranes, and a fluorometric method for continuous measurement of Ca2+ transport in membrane vesicles was developed. The results are discussed in relation to what is known about the Ca2+-ATPase in animal plasma membranes and to recent reports of the effect of trypsin treatment of the CaM-stimulated CaZf-ATPase in plasma membranes from radish seedlings (Rasi-Caldogno et al, 1993, 1995.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Fig. 3 also shows the response of WT and D291A ACA8 to controlled proteolysis with trypsin, which selectively cleaves the N terminus of plant PM Ca 2ϩ -ATPase (12,28,29). Under the applied conditions tryptic treatment of the membranes effectively, albeit not completely, cleaved the N terminus of WT and D291A ACA8 (Fig.…”
Section: Site-directed Mutagenesis Of Acidic Residues In the Smallmentioning
confidence: 99%
“…Various regulatory activities can relieve the auto-inhibition caused by this R domain. For example, the P2 B -ATPase subgroup, comprising the plasma membrane Ca 2ϩ pumps, contains an R domain in the C-terminal tail (in animals) (8,9,18) or in the N-terminal tail (in plants) (13)(14)(15)(16)19). When calmodulin interacts with this R domain, it displaces the autoinhibitory tail and activates the protein for Ca 2ϩ transport.…”
mentioning
confidence: 99%